Protective effect of brain microvascular endothelial cell-derived exosomes on blood-brain barrier induced by ischemia-reperfusion injury in vivo and in vitro - Sun, Jin; Wang, Meng; Guo, Lichen; Cao, Yushuang; Su, Linlin; Wang, Shaoxia; Chai, Lijuan; Yuan, Qing; Hu, Limin (Frontiers in Pharmacology, 2025)
BackgroundEnhanced blood-brain barrier (BBB) permeability exacerbates clinical symptoms and long-term disability after ischemic stroke. Exosomes derived from cerebral microvascular endothelial cells (EC-Exo) can enhance neural function recovery in MCAO/R mice. However, it remains unclear whether the brain protective effects of EC-Exo are associated with improved BBB structure and functionality.MethodsThis study developed an in vitro BBB model by co-culturing endothelial cells (bEnd.3) with pericytes (MBVP) to examine the effects of EC-Exo on BBB integrity. The neurobehavioral function of EC-Exo was evaluated in vivo using the rotarod test and gait assessment. The permeability of BBB was evaluated using the Evans blue penetration test and IgG leakage test. The integrity of the BBB structure was assessed using immunofluorescence and Western blot analysis. Mechanistic investigations aimed to elucidate the regulatory role of PDGF-PDGFRβ and Ang1/Ang2-Tie2 pathways in maintaining BBB integrity.ResultsEC-Exo improves BBB integrity by increasing TEER values and decreasing Papp in vitro. Besides, EC-Exo not only reduces gait abnormalities in MCAO/R-injured mice, attenuates BBB permeability in vivo. EC-Exo enhances the expression of tight junction and basement membrane proteins. Mechanistic studies have demonstrated that EC-Exo can effectively activate the PDGF-PDGFRβ and Ang1/Ang2-Tie2 signaling pathways, thereby facilitating the maintenance of BBB integrity, and these effects were verified with PDGFRβ inhibitor and Tie2 inhibitor in vitro.ConclusionIn conclusion, EC-Exo enhances BBB integrity by activating PDGF-PDGFRβ and Ang1/Ang2-Tie2 signaling pathways, promoting communication between endothelial cells and pericytes. This introduces an innovative adjuvant therapy for treating ischemic stroke.